Characterization of four common deafness gene mutations among 12 221 newborns delivered at four hospitals in a district of Suzhou city, 2018 - 2022 - Yuxing FAN; Hongqin GAO; Hong PAN; Yong XU; Hong ZHU (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo investigate the characteristics of common deafness gene mutations in newborns in a district of Suzhou municipality, Jiangsu province for the prevention and treatment of hereditary hearing loss.MethodsMicro blood samples were collected from 12 211 newborns delivered at four general hospitals in Suzhou High-Tech Zone from July 2018 through July 2022 for detections of 20 mutant loci of four common deafness genes GJB2 (35delG, 176_191del16, 235delC and 299_300delAT), GJB3 (538C > T and 547G > A), SLC26A4 (281C > T, 589G > A, IVS7-2A > G, 1174A > G, 1226G > A, 1229C > T, IVS15+5G > A, 1975G > C, 2027T > A, 2162C > T and 2168A > G) and mitochondrial 12SrRNA (1095T > C, 1494C > T and 1555A > G) with congenital deafness gene detection kit. Gender and yearly differences in detection rates of the deafness gene mutations among the newborns were analyzed.ResultsAmong 12 211 newborns, 680 (5.57%) were found to carry the 4 common deafness genes, with the detection rates of 2.80% for GJB2, 1.77% for SLC26A4, 0.67% for mitochondrial 12SrRNA, and 0.43% for GJB3, respectively. Of the 20 mutant loci detected, the detection rate was the highest (2.05%) for heterozygote 235delC mutation in GJB2 gene, followed by 1.16% for heterozygote IVS7-2A > G mutation in SLC26A4 gene. There were no significant yearly and gender differences in the total detection rate and the composition ratio of gene mutations among the neonates (all P > 0.05), but there was a significant yearly difference in the detection rate of mitochondrial 12SrRNA gene (P < 0.01) and a significant gender difference in the detection rate of GJB2 gene (P = 0.04). ConclusionAmong newborns in Suzhou High-Tech Zone, the dominantly detected deafness gene mutations were GJB2235delC and SLC26A4 IVS7-2A > G mutation. The total detection rate of common deafness genes did not significantly differ between male and female newborns and in different years but there were gender and yearly differences in gene-specific detection rate. The results should be considered in genetic screening for neonatal deafness.